Analisis sajian buku ajar fisika SMA kelas XII semester 1 terkait komponen contextual teaching and learning (CTL) - Firda Annisa; Desnita Desnita; Yenni Darvina; Asrizal Asrizal; zulhendri kamus (Universitas Negeri Padang, 2019)
This type of research is a descriptive study with a qualitative approach. The population data in this study were all physics textbooks for class XII high school students used by 17 schools in West Sumatra. Sampling was done by purposive sampling technique. The sample in this study was the most high school physics class XII semester 1 textbook used by schools published by four different publishers. The data in this study were taken using textbook presentation instrument analysis and data collection techniques through documentation studies.The results showed that the level of CTL feasibility in class XII semester 1 physics textbooks published by book A was 69.58% with the appropriate category, then the CTL grade performance in class XII semester 1 physics textbooks published by book B was 82 , 77% with a very appropriate category, then the level of CTL implementation in physics textbooks for class XII semester 1 published by book C was 58.13% which was categorized quite appropriate, and for the level of CTL implementation in physics textbooks in class XII semester 1 published by book D is 90.68% which is categorized very accordingly. The results of the study can be used as a needs analysis in developing research on the presentation of physics textbooks in implementing CTL